2002
DOI: 10.1002/jms.313
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between isomeric acacetin‐6‐C‐(6″‐O‐malonyl)glucoside and acacetin‐8‐C‐(6″‐O‐malonyl)glucoside by using low‐energy CID mass spectra

Abstract: Differentiation between isomeric acacetin-6-C-(6 -O-malonyl)glucoside and acacetin-8-C-(6 -O-malonyl)glucoside by using low-energy CID mass spectra Flavonoid conjugates constitute a very diversified group of plant secondary metabolites. These compounds reveal various type of biological activity. 1,2 Mass spectrometric techniques have been successfully used for the structural elucidation of flavonoid C-glycosides for more than 25 years. First, the flavonoid C-glycosides were analysed as permethyl ethers using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The fragment with m/z 97 was considered to be the sulfate moiety. On the other hand, those at m/z 259 and m/z 289 were considered to be the common fragments of glycoconjugates [18,19]. Our results of LC/ESI-MS/MS analysis and deconjugation indicated that peak-f was the glucose-sulfate conjugate of 1-hydroxypyrene.…”
Section: Structure Of the New Phase-2 Metabolite (Peak-f) Formed By Fmentioning
confidence: 67%
See 2 more Smart Citations
“…The fragment with m/z 97 was considered to be the sulfate moiety. On the other hand, those at m/z 259 and m/z 289 were considered to be the common fragments of glycoconjugates [18,19]. Our results of LC/ESI-MS/MS analysis and deconjugation indicated that peak-f was the glucose-sulfate conjugate of 1-hydroxypyrene.…”
Section: Structure Of the New Phase-2 Metabolite (Peak-f) Formed By Fmentioning
confidence: 67%
“…On the other hand, Stroomberg et al [18] determined the structure of a conjugation metabolite of pyrene formed by isopods (Porcellio scaber) and collembolans (Folsomia candida) as pyrene-1-O-(6"-O-malonyl)-glucoside, which is the first reported conjugate formed by animals. On the other hand, malonyl-glycosides are well-known conjugation products formed by plants [19][20][21][22][23][24]. Glucose conjugates formed by various plants are often further conjugated by malonic acid or pentosyl units of hemicellulose, such as apiose or xylose, and form glucose-malonate or glucose-pentosyls [19][20][21][22][23][24].…”
Section: The Role Of Glucose-sulfate Conjugation Formed By Freshwatermentioning
confidence: 99%
See 1 more Smart Citation
“…C-8)-apigenin. 20,21 Also, the success of proposed rules to differentiate C-isomers is relatively limited to the particular type of instrument and experimental conditions of the spectra used to generate those guidelines. So it is advisable to obtain ones own rules and guidelines in other types of instruments.…”
Section: X]mentioning
confidence: 99%
“…We have isolated and identified several flavonoids [6][7][8][9] and phenolic acids [10,11] in the aerial parts of the plant as well as alkaloids in roots [12]. The predominant compound was 4'-methoxy-5,7-dihydroxyflavone 6-C-glucopyranoside (isocytisoside) [6].…”
Section: Experimental Designmentioning
confidence: 99%